Pleasant memories: remembering immune protection while forgetting about graft-versus-host disease - Sondel, Paul M. (American Society for Clinical Investigation, 2003)
Graft-versus-host disease (GVHD) represents a major cause of morbidity and mortality following conventional allogeneic hematopoietic stem cell transplantation (HSCT). A study in mice (see related article on pages 101–108) demonstrates that the selective administration of donor memory CD4(+) T cells results in immune reconstitution without GVHD, a result that, if translatable to humans, has important clinical implications for HSCT.